Desenvolvimento e avaliação toxicológica de filmes comestíveis hidrofóbicos com incorporação de nanopartículas de quitosana - Scramin, Juliana Aparecida (2013)
The sweet sorghum is being evaluated as an alternative for the production ethanol during between harvest the sugar cane crop residue and part of this production consists of grains, rich in storage proteins, known as kafirins. In this work were extracted and characterized the kafirins of sweet sorghum cultivar BR 501 (white) free of tannins, with and without reducing agent, and the same were characterized by gel electrophoresis containing sodium dodecyl sulfate (SDS/PAGE). The secondary structures of kafirins were studied by spectroscopic techniques such as Fourier transform infrared and solid state 13C nuclear magnetic resonance (continue...).